Draft Annual Plan 1982-83 Government of Bihar - Planning Commission (Planning Commission, 1982)
Bihar is the 7th largest State in the Indian Union in terms of area and 2nd largest in terms of population. Although Bihar has only 5.3 per cent of the area of the country, 10.21 per cent of the total population of the country reside within the State. There are three district agro-climatic zones in the State. The North Bihar plan which lies to the north of the Ganges has 30.9 per cent of the area and 45.02 per cent of the population of the State. The South Bihar plan occupies 23.3 per cent of the area and have 29.8 per cent of the population of the State. The South Bihar plateau, on the other hand, has an area which is 45.8 per cent of the State area but has a population which is only 25.16 per cent of the total population.
Planning Department